Long-term culture and cloning of nontransformed human B lymphocytes (The Rockefeller University Press, 1981)
B lymphocyte-enriched cell populations cultured with mitogens in initial suspension cultures formed colonies in soft agar when the same mitogenic agent was present in the lower layer of a two-layer soft agar system. Colony formation depended upon the presence of T cells in the initial culture, and was optimal after an initial 72-h culture with phytohemagglutinin (PHA; 12.5 microliters/ml), pokeweed mitogen (PWM; 2.5 micrograms/ml), or protein A (10 micrograms/ml). The colonies could be picked from the agar and propagated by feeding every 3 d with medium supplemented with a growth factor-containing tissue culture supernate. The growth factor-containing supernate was prepared by stimulating pools of human peripheral blood mononuclear cells for 72 h with PHA or PWM. The lines propagated in this manner were membrane Ig+, lacked sheep erythrocyte rosette-forming ability, and did not ingest latex. They lacked the Epstein-Barr nuclear antigen (EBNA) and had 46 chromosomes. Such lines have been propagated for over 1 yr. One line (BL1) was subjected to limiting dilution cloning and a line, BL1.1, was prepared that contained 96% lambda-bearing cells and no kappa-bearing cells. This line was also EBNA negative. This procedure can thus be used to prepare and clone long-term lines of nontransformed human B lymphocytes.